Pengaruh Pemberdayaan Usaha Kecil Terhadap Peningkatan Pendapatan Usaha di Kecamatan Singkil Kota Manado - Jacobs, Feiby Pisga; Posumah, Jhonny Hanny; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2015)
Small business sector has been recognized as having a vital role in proving the nations economy. Because it is expected the government can give special attention to small businesses. This needs to be done by the government because most businesses in Indonesia belloging to small businesses. The phenomenon of the low quality of human resources for small businesses almost uniformly in all regions of Indonesia. This applies also for those belonging to small businesses in the district. Because it attemps to foster the entrepereneurial spirit for small businesses is something that should be done to increase growth have to a little better so as to change the status of its business at the same effect on the increase in their income.This study aimed to analyzed the relationship between the empowerment of small businesses to increase revenues in the District of Singkil in Manado City by using purposive sampling and analysis of how to carry out the data collection is questioner.Intepolation methods in order to predict the value of the variable income of small businesses (Y) (Sudjana, 1983). By using statistical tools for data processing assisted by computers throught the program SPSS version 20 for Windows.Factors strengthening human resources throught the provision of the venture capital loans partially contribute positively and significantly to the income of the small businesses. Keyword: Empowering Small Businesses, Increase Revanues